Yellowstone ranger : stories from a life spent with bears, backcountry, horses, and mules, from Yosemite to Yellowstone /: stories from a life spent with bears, backcountry, horses, and mules, from Yosemite to Yellowstone. (2023) - Mernin, Jerry, 1912-2011
No abstract available